2020
DOI: 10.1536/ihj.19-327
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Reduces Ventricular Arrhythmia Activity and Calcium Sparks-Mediated Sarcoplasmic Reticulum Ca Leak in Rats with Heart Failure

Abstract: The aim of this study was to investigate the effect of exendin-4 (Ex-4) on ventricular arrhythmias and calcium sparks-mediated calcium leak in a myocardial infarction-heart failure model. We studied the influence of exendin-4 on ventricular arrhythmogenesis in a rat myocardial infarction-heart failure model. In vivo arrhythmia studies (electrocardiogram [ECG] telemetry studies), ex vivo arrhythmia studies calcium sparks tests, and analysis of total and phosphorylated ryanodine receptor (RyR) 2 and CaMK-II were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Direct acute perfusion of 100 ng/mL FGF-23 reduced systolic Ca 2+ release and increased the spontaneous diastolic Ca 2+ leak, increasing the incidence of arrhythmogenic Ca 2+ events (Navarro-García et al, 2019). This phenotype is frequently observed in failing cardiomyocytes (Ruiz-Hurtado et al, 2015;Alvarado et al, 2017;Chen et al, 2020), which might explain the relationship between FGF-23 levels and HF incidence described previously in this review. The events observed in cells are strongly influenced by Ca 2+ mishandling and could be induced by RyRs hyperactivity and a reduction in SERCA activity, both of which are responsible for reduced SR Ca 2+ load (Navarro-García et al, 2019).…”
Section: Fgf-23 Causes Cardiac Dysfunctionsupporting
confidence: 68%
“…Direct acute perfusion of 100 ng/mL FGF-23 reduced systolic Ca 2+ release and increased the spontaneous diastolic Ca 2+ leak, increasing the incidence of arrhythmogenic Ca 2+ events (Navarro-García et al, 2019). This phenotype is frequently observed in failing cardiomyocytes (Ruiz-Hurtado et al, 2015;Alvarado et al, 2017;Chen et al, 2020), which might explain the relationship between FGF-23 levels and HF incidence described previously in this review. The events observed in cells are strongly influenced by Ca 2+ mishandling and could be induced by RyRs hyperactivity and a reduction in SERCA activity, both of which are responsible for reduced SR Ca 2+ load (Navarro-García et al, 2019).…”
Section: Fgf-23 Causes Cardiac Dysfunctionsupporting
confidence: 68%
“…This is of interest, as GLP1R agonists have been implicated in preserving proper cardiac remodelling and shown to be cardioprotective following insults such as myocardial infarcts or ischaemia. [83][84][85] Moreover, GLP1R has shown to be essential for HR control in mice, and thus, its severe down-regulation in tumour hosts in this study may be responsible in part for cardiac dysfunction. 86 Additionally, SCGB1A1, also known as uteroglobin, was reduced 70-fold in tumour-bearing mice and increased 44 678-fold in tumour mice receiving ACVR2B/Fc.…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, GLP1R was reduced 51‐fold in the tumour‐bearing mice and increased 71‐fold in ACVR2B/Fc‐treated HCT116 hosts. This is of interest, as GLP1R agonists have been implicated in preserving proper cardiac remodelling and shown to be cardioprotective following insults such as myocardial infarcts or ischaemia 83–85 . Moreover, GLP1R has shown to be essential for HR control in mice, and thus, its severe down‐regulation in tumour hosts in this study may be responsible in part for cardiac dysfunction 86 .…”
Section: Discussionmentioning
confidence: 77%
“…MI, myocardial infarction; Ex-4, exendin-4; Ex9-39, exendin9-39; GLP-1, glucagon-like peptide-1 receptor; p-, phosphorylated; t-, total. studies showed that exendin-4 has direct electrophysiological effect on electrocardiogram parameters including QRS, QT and QTc intervals and calcium handling in ventricular arrhythmias (9,20). However, limited information is available regarding the effects of exendin-4 on atrial electrophysiology in heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective effects of exendin-4 are well known and a previous study by the authors demonstrated the cardioprotective effects of exendin-4 on a rat model of chronic MI through the endothelial nitric oxide synthase/cyclic guanosine monophosphate/protein kinase G pathway ( 9 ). Our previous studies showed that exendin-4 has direct electrophysiological effect on electrocardiogram parameters including QRS, QT and QTc intervals and calcium handling in ventricular arrhythmias ( 9 , 20 ). However, limited information is available regarding the effects of exendin-4 on atrial electrophysiology in heart failure.…”
Section: Discussionmentioning
confidence: 99%